2016
DOI: 10.1002/joc.4733
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the importance of spatio‐temporal RCM resolution when estimating sub‐daily extreme precipitation under current and future climate conditions

Abstract: Overall, the results from this study show the influence of the spatial resolution on the precipitation 1 outputs from RCMs. The biases of the RCM simulations increase and the projected changes 2 decrease for decreasing spatial resolution of the simulations. This points towards the need for high 3 spatial and temporal resolution RCMs to obtain reliable information on changes in sub-daily 4 extreme precipitation. 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 61 publications
6
32
0
Order By: Relevance
“…The final conversion factor to go from a near instantaneous point source rain gauge measurement to the 1 h and 0.11 • resolution model data becomes the product of the time reduction factor of the gauge data and the space and time reduction factor of HIPRAD, as shown in the last line of Table 2. These factors compare well to previously applied area reduction factors (Sunyer et al, 2016), e.g. (Wilson, 1990) presented a factor 1.279 for hourly precipitation, although at 24 h duration the factor only decreased to 1.066 indicating a slightly too small factor in our current study.…”
Section: Comparison Across Spatio-temporal Scalessupporting
confidence: 90%
See 1 more Smart Citation
“…The final conversion factor to go from a near instantaneous point source rain gauge measurement to the 1 h and 0.11 • resolution model data becomes the product of the time reduction factor of the gauge data and the space and time reduction factor of HIPRAD, as shown in the last line of Table 2. These factors compare well to previously applied area reduction factors (Sunyer et al, 2016), e.g. (Wilson, 1990) presented a factor 1.279 for hourly precipitation, although at 24 h duration the factor only decreased to 1.066 indicating a slightly too small factor in our current study.…”
Section: Comparison Across Spatio-temporal Scalessupporting
confidence: 90%
“…Olsson et al (2015) presented increasing agreement of modelled and observed hourly precipitation with higher spatial resolution, and 6 km resolution of a parametrised RCM (RCA3) is in approximate agreement with gauge observations. Similar results were obtained for Denmark, where also future projections were found to show larger increases in extreme precipitation for higher spatial resolution and shorter temporal aggregations (Sunyer et al, 2016). Convective permitting regional models at less than about 5 km resolution, have been shown to better simulate the peak structure of extreme events (Kendon et al, 2014), better agreement with observations regarding the diurnal cycle of precipitation intensity (Fosser et al, 2015;Prein et al, 2015), as well as improved performance of extreme hourly events (Ban et al, 2018).…”
supporting
confidence: 74%
“…This is in spite of the similarities of several of the models. For example, the convective parameterization is similar for HIRHAM5, REMO2009, and RACMO22E, which are all based on Tiedtke (1989) but with differences in their settings and in additions to the parameterizations. Further, HIRHAM5, RACMO22E, and RCA4 share similar dynamical cores (originating from the HIRLAM NWP model).…”
Section: Discussionmentioning
confidence: 99%
“…The determined threshold values for each GCM historical run are also applied to the future scenarios that enables the future runs to have a different wet day frequency compared to the historical runs. In this study, 0.1 mm is considered as a threshold of the observations to distinguish a wet day from a dry day (Olsson et al ., ; Sunyer et al ., ; Gudmundsson et al ., ) and determines the frequency of wet days. For consistency, rainfall amounts in observations and simulations are all set to 0 mm when they are smaller than the specific thresholds.…”
Section: Methodsmentioning
confidence: 99%